2022
DOI: 10.3389/fgene.2022.1047004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of M1 macrophage-related genes identification in bladder urothelial carcinoma and in vitro validation

Abstract: Background: Tumor microenvironment (TME) takes a non-negligible role in the progression and metastasis of bladder urothelial carcinoma (BLCA) and tumor development could be inhibited by macrophage M1 in TME. The role of macrophage M1-related genes in BLCA adjuvant therapy has not been studied well.Methods: CIBERSOR algorithm was applied for identification tumor-infiltrating immune cells (TICs) subtypes of subjects from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data sets. We identified po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Understanding the immune cell infiltration within the TME is crucial for comprehending the immune evasion mechanisms of tumors and providing insights into personalized treatment strategies. By gaining in-depth knowledge of immune infiltration in the tumor microenvironment, treatment regimens can be optimized, leading to improved clinical outcomes ( Chen et al, 2022 ; Yu et al, 2022 ). It has been shown that the activation of tumor-infiltrating CD8T cells is significantly increased after resveratrol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the immune cell infiltration within the TME is crucial for comprehending the immune evasion mechanisms of tumors and providing insights into personalized treatment strategies. By gaining in-depth knowledge of immune infiltration in the tumor microenvironment, treatment regimens can be optimized, leading to improved clinical outcomes ( Chen et al, 2022 ; Yu et al, 2022 ). It has been shown that the activation of tumor-infiltrating CD8T cells is significantly increased after resveratrol treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram was developed using the ‘rms’ package in R, and its visualization was performed with the ‘regplot’ package [ 19 ]. The model integrated the risk scores from the nomogram and the clinical characteristics of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the ESTIMATE algorithm and CDC45 expression matrix, the ImmuneScore, StromalScore, and ESTIMATEScore were calculated (Yu et al 2022 ). TIMER was employed to examine the relationships between CDC45 and immune cell infiltration in KIRC (TIMER, https://cistrome.shinyapps.io/timer/ ) (Chen et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%